Economics And Religion: Are They Distinct? - Brennan, H. Geoffrey (Recent Economic Thought Series, 1994)
What is the relation between economics and religion? In particular, are theology and economics entirely autonomous and distinct areas of inquiry? Economics and Religion: Are They Distinct? takes an inductive approach using case studies to shed light on the extent to which economics may be regarded as independent of the religious beliefs of its practitioners. The case studies comprise the first part of the book and are listed chronologically. These case studies are followed by commentaries, or interpretive essays; the authors of these commentaries are acting as a jury to consider the question `How sensitive is economics to theological considerations?' The editors provide a concluding chapter summarizing both the evidence and the findings